Development Of Biotechnology Teaching Materials: E-Comics Complemented by Factual Videos to Improve Science Literacy Skills - Wahyuni Lubis; Diky Setya Diningrat; Ashar Hasairin; Muhammad Azhari; Adi Hartono (Jurnal Penelitian Pendidikan IPA, 2024)
Biotechnology might be difficult to understand. Comics were learning media that presented the material in the form of illustrated stories to make it more interesting, fun, not boring, and easily understood by students. Innovation makes comics in digital form, namely e-comics equipped with factual videos. The purpose of this study was to determine the feasibility of biotechnology e-comics equipped with factual videos, as well as the readability and response of students to biotechnology e-comics media equipped with factual videos. This research uses the ADDIE development model starting from the analysis, design, development, implementation, and evaluation stages. The samples used in this study were randomly selected XII-grade students of Sultan Daulat 1 Senior High School. Based on the research that has been done, the results obtained are: 1) Biotechnology e-comic media complemented by factual videos obtained a material validation score of 84% and media validation obtained a score of 93% with a very valid category. 2) Comic media obtained a readability score of 81.4% with a very good category 3) Students' responses to comic media obtained a score of 82% in the very good category. Based on these results, the biotechnology e-comic media equipped with factual videos is categorized as very valid, so it is feasible to use it as a learning media.